New species of Kontrimavichusia Makarikov & Binkienė, 2022 (Eucestoda: Hymenolepididae) from arvicoline rodents (Rodentia: Cricetidae) from the North Caucasus - Makarikov, Arseny A.; Stakheev, Valeriy V. (European Journal of Taxonomy, 2024)
Two previously unrecognized species attributable to the genus Kontrimavichusia Makarikov & Binkienė, 2022 in arvicoline rodents from the North Caucasus are described. Kontrimavichusia testiculata sp. nov. is described from Microtus majori (Thomas, 1906) from the northwestern Caucasus (Republic of Adygeya and Karachay-Cherkess Republic, Russia) and Kontrimavichusia hobergi sp. nov. is described from Microtus daghestanicus (Shidlovsky, 1919) from the central Caucasus (Republic of North Ossetia, Russia). Kontrimavichusia testiculata is readily distinguishable from K. asymmetrica (Janicki, 1904) and K. hobergi in having a larger number of testes (4–6 per proglottis), larger suckers and a longer cirrus and cirrus-sac. In addition, the new species differs from its congeners by the position of the cirrus-sac with regard to the poral osmoregulatory canals and position of distal end of the rostellar pouch relative to the posterior margins of the suckers. Kontrimavichusia hobergi can be readily distinguished from its congeners by the arrangement of the testes in a triangle and the position of the cirrus-sac with regard to the poral osmoregulatory canals. In addition, this previously unrecognized species differs from K. asymmetrica and K. testiculata by the smaller dimensions of the fully developed strobila and a narrower ovary. The cirrus-sac of K. hobergi is larger than that in K. asymmetrica but smaller than that in K. testiculata. We also used partial sequences of the nuclear ribosomal 28S rRNA gene and mitochondrial nad1 gen to justify the generic arrangement and independent status of these two new species which are characterized in the current manuscript.